2018
DOI: 10.1016/j.cjtee.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Locking plate versus external fixation for type C distal radius fractures: A meta-analysis of randomized controlled trials

Abstract: PurposeDistal radial fracture is one of the most common fractures. Up to now, locking plates (LP) and external fixation (EF) are two conventional surgical approaches to type C radius fracture. Which method is superior has not yet reached a consensus. We try to assess the clinical effectiveness of the two interventions by this meta-analysis.MethodsWe used network to search the PubMed, Embase, and Cochrane Medical Library of randomized controlled clinical trials about the type C distal radius fractures performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous research has demonstrated that this is accomplished by accurately reducing normal radial inclination, radial height, and volar tilt, and as a result, radial articular step with reduction of the distal radioulnar joint in intra-articular fractures [38,39]. When compared with lockig plate, the radiological examination revealed that the BEF group had a poorer radial inclination [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that this is accomplished by accurately reducing normal radial inclination, radial height, and volar tilt, and as a result, radial articular step with reduction of the distal radioulnar joint in intra-articular fractures [38,39]. When compared with lockig plate, the radiological examination revealed that the BEF group had a poorer radial inclination [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that this is accomplished by accurately reducing normal radial inclination, radial height, and volar tilt, and as a result, radial articular step with reduction of the distal radioulnar joint in intra-articular fractures [ 38 , 39 ]. When compared with lockig plate, the radiological examination revealed that the BEF group had a poorer radial inclination [ 7 ].Comparing dynamic EF with static bridging or non-bridging EFs, no notable anatomic or clinical difference was found [ 40 , 41 ]. However, the concept with developing and applying dynamic EF was early mobilization in prior research, rather than optimizing the force direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…External fixation (EF) is a valid and simple method used for fixing unstable DRFs. A recent meta-analysis has shown that there were no significant different clinical outcomes in AO/OTA C-type managed with locking plates, compared with EF 10 . Modular external bridging fixator has replaced the previous fixed bridging, ensuring rapid mobilisation 11 .…”
Section: Introductionmentioning
confidence: 99%